Parental Disengagement in Childhood and Adolescent Male Gun Carrying - Beardslee, Jordan (Pediatrics, 2019)
[Figure: see text] OBJECTIVES: To examine the association between parental disengagement in childhood and adolescent gun carrying and determine whether this association is accounted for by externalizing problems and affiliation with delinquent peers during early adolescence. METHODS: The sample included 503 boys (55.7% African American, 40.6% white, 3.7% other) recruited from first-grade classrooms in Pittsburgh public schools. Multi-informant assessments were conducted regularly (semiannually then annually) from approximately ages 7.5 to 20 years. Latent factors were constructed by using parent-reported parental disengagement (ie, poor parental involvement, poor parent-son communication, poor parent-son relationship quality) collected from ages 7.5 to 10 years, youth-reported peer delinquency from ages 10.5 to 13 years, and teacher-reported externalizing problems from ages 10.5 to 13 years. The outcome was youth-reported gun carrying from ages 14 to 20 years. RESULTS: Twenty percent of individuals sampled reported carrying a gun during adolescence. Childhood parental disengagement was significantly associated with adolescent gun carrying (β = .22; 95% confidence interval: 0.08 to 0.36). Furthermore, the association between parental disengagement and gun carrying was partially mediated through peer delinquency and externalizing problems during early adolescence. The 2 indirect paths accounted for ∼29% of the total effect of parental disengagement. CONCLUSIONS: Boys exposed to poorer parental engagement during childhood are more likely to affiliate with delinquent peers and exhibit externalizing problems during early adolescence, which (in turn) increases their risk of carrying a firearm in later adolescence. This suggests that gun violence prevention efforts with children should work to enhance aspects of parental engagement.